Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/j.eupc.2003.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler monitoring during head upright tilt table testing in patients with suspected neurocardiogenic syncope

Abstract: The aim of the present study was to evaluate the mechanism of cerebrovascular autoregulation in patients with neurocardiogenic syncope using bilateral transcranial Doppler (TCD) monitoring during head upright tilt table testing (HUT). Two hundred and six patients were prospectively studied. One hundred and fifty-nine subjects (77%) had a prior history of syncope and 47 (23%) had presyncope. Ninety-nine patients (48%) had syncope or presyncope during HUT with a 76% fall in diastolic middle cerebral artery blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
1
19
1
Order By: Relevance
“…The findings provide important information regarding grayor black-out incidents that occur immediately at the cessation of exercise (5,8) and are consistent with previous studies (2,22) that have reported that syncope was related to impaired regulation of the diastolic phase of MCA V. When blood pressure decreases during syncope, MCA Vd diminishes, whereas MCA Vs may be well maintained (22). In addition, during head-up tilt, MCA Vs and MCA Vd fall significantly.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings provide important information regarding grayor black-out incidents that occur immediately at the cessation of exercise (5,8) and are consistent with previous studies (2,22) that have reported that syncope was related to impaired regulation of the diastolic phase of MCA V. When blood pressure decreases during syncope, MCA Vd diminishes, whereas MCA Vs may be well maintained (22). In addition, during head-up tilt, MCA Vs and MCA Vd fall significantly.…”
Section: Discussionsupporting
confidence: 88%
“…Rather, our findings suggest that the influence of CA on MCA Vd is different from MCA Vs during exercise and recovery. These differential CA influences may be important physiologically because previous studies have already demonstrated that there is a different response of MCA V to change in perfusion pressure between systolic and diastolic phases during specific conditions, such as orthostatic stress (2,22) and exercise (18,21). Although both transfer function phase and gain are used as an index of dynamic CA, changes in gain were not consistent with changes in phase in the present study.…”
Section: Discussioncontrasting
confidence: 62%
“…Previously established age-appropriate depths were used to insonate both the MCAs and BAs. 4 During steady-state conditions, Vmca, Vbas, mean arterial pressure (MAP), heart rate, and respiratory rate were recorded in each position.…”
Section: Study Design and Protocolmentioning
confidence: 99%
“…6,[13][14][15][16] Transcranial Doppler ultrasound has been used in several studies investigating autoregulation. 3,8,14,[17][18][19] However, TCD studies of orthostatic blood flow changes in patients with stroke are limited. 20,21 Ischemic stroke typically is caused by occlusion of a cerebral blood vessel 22 (commonly the middle cerebral artery [MCA]).…”
mentioning
confidence: 99%